Low-temperature time-resolved spectroscopic study of the major light-harvesting complex of Amphidinium carterae - Slouf, Václav; Fuciman, Marcel; Johanning, Silke; Hofmann, Eckhard; Frank, Harry A; Polívka, Tomáš (Photosynthesis research, 2013)
The major light-harvesting complex of Amphidinium (A.) carterae, chlorophyll-a-chlorophyll-c 2-peridinin-protein complex (acpPC), was studied using ultrafast pump-probe spectroscopy at low temperature (60 K). An efficient peridinin-chlorophyll-a energy transfer was observed. The stimulated emission signal monitored in the near-infrared spectral region was stronger when redder part of peridinin pool was excited, indicating that these peridinins have the S1/ICT (intramolecular charge-transfer) state with significant charge-transfer character. This may lead to enhanced energy transfer efficiency from "red" peridinins to chlorophyll-a. Contrary to the water-soluble antenna of A. carterae, peridinin-chlorophyll-a protein, the energy transfer rates in acpPC were slower under low-temperature conditions. This fact underscores the influence of the protein environment on the excited-state dynamics of pigments and/or the specificity of organization of the two pigment-protein complexes.
Keywords: Electrons; elektrony; blízká infračervená spektroskopie; Energy Transfer; Chlorophyll; přenos energie; Time Factors; chlorofyl; kinetika; Light-Harvesting Protein Complexes; Carotenoids; Dinoflagellida; časové faktory; Dinoflagellata; světlosběrné proteinové komplexy; nízká teplota; Kinetics; Cold Temperature; Spectroscopy, Near-Infrared; karotenoidy